Markerless 3D motion analysis system - Adachi, K.; Ishimoto, A.; Honda, N. (14th International Symposium on 3D Analysis of Human Movement, 2016)
It is necessary among most of the conventional 3D motion analysis systems to attach light reflecting markers to the specified position of the body. This procedure is time-consuming work and needs expert knowledge of human somatology. To avoid this procedure we developed a markerless 3D motion analysis system called "Anakin System" using three Kinect v1 sensors. The calibration method to unify the coordinate system of each sensor is unique and easy. The accuracy of this system was examined by comparing 3D position data of the lower limb joints measured at the same time during the gait by Anakin System and Vicon System which needs markers. The 3D position data measured by Anakin System are in well accordance with the data measured by Vicon System. Anakin System can measure motions of plural subjects independently at the same time. But as inadequate specification its sampling rate is 30 times per second.